Selfishness and selflessness : new approaches to understanding morality - Layne, Linda L. (Wyse series in social anthropology ;, 2020)
"We are said to be suffering a narcissism epidemic when the need for collective action seems more pressing than ever. Selfishness and selflessness address the 'proper' and 'improper' relationship between one's self and others. The work they do during periods of social instability and cultural change is probed in this original, interdisciplinary collection. Contributions range from an examination of how these concepts animated the eighteenth-century anti-slavery campaigners to dissecting the way middle-class mothers' experiences illustrate gendered struggles over how much and to whom one is morally obliged to give"--